KAJIAN PEMANFAATAN LIMBAH PADAT SUMUR MINYAK LAPANGAN KAWENGAN MENINGKATKAN PEROLEHAN MINYAK DENGAN CARA DI EKSTRAKSI - Semy Sinay; Erdila Indriani; Noce N Tetelepta (Department of Mechanical Engineering, 2025)
In oil and gas industry activities, the oil and gas processing process will produce waste, one of which is oil solid waste, which is waste that comes from the production and processing process of petroleum in the oil field because it is one of the supports for the Cepu refinery which has several old wells that are still actively producing to this day, thus the use of waste oil is very necessary. With the amount of TPH obtained from waste oil, which is 48.10%, there is potential to be extracted. The method used is a simple heating method to separate hydrocarbons from waste solids. After the extraction test was carried out and associated with the results of the oil composition test, the saturated composition was obtained 48.84%, aromatic 23.59%, resin 25.91% and asphaltene 1.66% where this composition has an influence on the results of the hydrocarbon extraction test from waste oil. With simple heating using an oven, the results obtained are not significant as the extracted oil hardens again. After heating, the light fraction of saturated oil is released while the heavy fraction, resin and aromatics, as well as impurities, affect the hardening of the sample at room temperature. Kaywords: Solid Waste, Oil, Extraction